2009
DOI: 10.1152/ajpregu.00280.2009
|View full text |Cite
|
Sign up to set email alerts
|

Maternal low-protein diet alters pancreatic islet mitochondrial function in a sex-specific manner in the adult rat

Abstract: Theys N, Bouckenooghe T, Ahn M-T, Remacle C, Reusens B. Maternal low-protein diet alters pancreatic islet mitochondrial function in a sex-specific manner in the adult rat. Am J Physiol Regul Integr Comp Physiol 297: R1516 -R1525, 2009. First published September 16, 2009; doi:10.1152/ajpregu.00280.2009.-Mitochondrial dysfunction may be a long-term consequence of a poor nutritional environment during early life. Our aim was to investigate whether a maternal low-protein (LP) diet may program mitochondrial dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
76
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 70 publications
(98 reference statements)
11
76
1
2
Order By: Relevance
“…The higher TAC found in LPHCprogramed animals is in agreement with previous studies showing that protein restriction during lactation induced an up-regulation of antioxidant defense capacity at adulthood, represented by increased expression of kidney antioxidant enzymes: glutathione peroxidase and glutathione reductase in 3-month-old rats and glutathione peroxidase, glutathione reductase, and manganese SOD in 1-year-old rodents (Tarry-Adkins et al 2007, Chen et al 2009a. On the other hand, other studies had associated protein restriction during neonatal life with increased oxidative stress and related detrimental effects (Fetoui et al 2009, Theys et al 2009. It has been shown that low-protein diets during gestation or gestation and lactation could predispose to pancreatic islet dysfunction later in life by an imbalance between higher concentration of superoxide radical-inactivating enzymes (SOD) and very low concentration of hydrogen peroxideinactivating enzymes (CAT and GPX) in islets of the progeny in 3-month-old rats (Theys et al 2009).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The higher TAC found in LPHCprogramed animals is in agreement with previous studies showing that protein restriction during lactation induced an up-regulation of antioxidant defense capacity at adulthood, represented by increased expression of kidney antioxidant enzymes: glutathione peroxidase and glutathione reductase in 3-month-old rats and glutathione peroxidase, glutathione reductase, and manganese SOD in 1-year-old rodents (Tarry-Adkins et al 2007, Chen et al 2009a. On the other hand, other studies had associated protein restriction during neonatal life with increased oxidative stress and related detrimental effects (Fetoui et al 2009, Theys et al 2009. It has been shown that low-protein diets during gestation or gestation and lactation could predispose to pancreatic islet dysfunction later in life by an imbalance between higher concentration of superoxide radical-inactivating enzymes (SOD) and very low concentration of hydrogen peroxideinactivating enzymes (CAT and GPX) in islets of the progeny in 3-month-old rats (Theys et al 2009).…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, other studies had associated protein restriction during neonatal life with increased oxidative stress and related detrimental effects (Fetoui et al 2009, Theys et al 2009. It has been shown that low-protein diets during gestation or gestation and lactation could predispose to pancreatic islet dysfunction later in life by an imbalance between higher concentration of superoxide radical-inactivating enzymes (SOD) and very low concentration of hydrogen peroxideinactivating enzymes (CAT and GPX) in islets of the progeny in 3-month-old rats (Theys et al 2009). In addition, proteinrestricted diet given to mothers during late pregnancy and early postnatal periods induced oxidative stress in their pups on postnatal d14 (Fetoui et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, mitochondrial compensatory mechanisms would likely be mobilized in several organs of FR30 fetuses, and we can postulate that fetal organ mitochondrial abnormalities might persist in adult FR30 rats. In accord with this hypothesis, long-term mitochondrial dysfunctions have been demonstrated in the pancreatic ␤-cells of rats prenatally exposed to a low-protein diet (28,32). To conclude, growing evidence suggests that mitochondrial dysfunctions may be implicated in several metabolic diseases, such as type 2 diabetes (21), obesity (18), and vascular diseases (27), and our present findings suggest that placental mitochondrial defects may also be implicated in part in the etiology of fetal growth restriction.…”
Section: Discussionsupporting
confidence: 86%
“…Using a maternal low-protein diet rat model, the expression of malate dehydrogenase, as well as the mitochondrial DNA-encoded subunit 6 of ATP synthase, was lower in the pancreatic islets, reducing the capacity of ATP production through mitochondrial oxidative metabolism. Interestingly, in agreement with our results, several consequences of protein restriction during fetal life were more marked in male offspring (60).…”
Section: Discussionsupporting
confidence: 93%